2010
DOI: 10.1080/13502930903520090
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ attitudes towards mathematics in early childhood education

Abstract: In Germany during the past few years the nursery school (for ages three-six) is increasingly regarded as an educational institution rather than a childcare centre. This is reflected in the increasing number of curricula for young children, which include mathematics as a domain of learning skills. In the past mathematics has not been part of the curriculum for training nursery school teachers. Therefore it is not clear what the teachers' understanding of mathematics is. Do they feel open or reluctant towards ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0
16

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 9 publications
6
43
0
16
Order By: Relevance
“…Anders and Rossbach (2015) also found that teachers did not have more negative attitudes towards mathematics than other professions (Baroody, Lai, & Mix, 2006). These results also coincide with the conclusion that in Thiel's (2010) study in Germany, most preschool teachers are open minded towards mathematics.…”
Section: Conclusion and Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Anders and Rossbach (2015) also found that teachers did not have more negative attitudes towards mathematics than other professions (Baroody, Lai, & Mix, 2006). These results also coincide with the conclusion that in Thiel's (2010) study in Germany, most preschool teachers are open minded towards mathematics.…”
Section: Conclusion and Discussionsupporting
confidence: 88%
“…In this study, it is found that while the teachers with positive attitudes towards teaching mathematics and mathematics encourage students frequently in the teaching process, teachers who have math anxiety and negative attitudes spend significantly less time on mathematics. Children who do not have enough math applications for their mathematical development remain at a low level in this area (Thiel, 2010). Lee (2005) examined the relationship between the attitudes of 81 preschool teachers towards mathematics and their mathematical practice.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2006). Bu sonuçlar Thiel (2010)'in Almanya'da yaptığı araştırmasında çoğu okul öncesi öğretmenlerin matematiğe karşı açık fikirli olduğu sonucu ile de örtüşmektedir.…”
Section: Tartişma Sonuç Ve öNeri̇lerunclassified